DISKURSUS KREATIVITAS PENDIDIK DALAM PEMILIHAN MODEL PEMBELAJARAN PPKN - Putri, Dian Eka (PKn Progresif, 2017)
ABSTRACTThe purpose of this study was to examine the importance of teacher creativity in the selection of Civic Education learning model. Based on the phenomena of Civic Education learning that seem monotonous, boring and uninteresting, thus demanding teachers to be more creative in the selection of learning models.The results of the study explained that the study of the creativity of educators (teachers) is still minimal and should continue to be improved. The results of in-depth research on the creativity of educators, conducted by Herman Yanzi (2014) on teacher creativity in learning, show results that have not been significant to the label of professional teachers with teacher performance. To be a creative teacher in the selection of Civic Education learning model, the teacher must first understand about the main components in learning PPKn that is civic knowledge, civic skills, and civic disposition. An educator in the field of Civic Education must understand the concept of these components to further formulate the process and learning objectives in learning tools.Educators' creativity is very important for ongoing learning in accordance with KI-KD and certainly in accordance with the objectives formulated. The creativity of educators in choosing the learning model should be based on the learning tools to be implemented. The conformity of KI-KD, and the learning material becomes a crucial part for educators to determine creative learning modelsKeywords: Discourse, Teacher Creativity, Model, Civic Education